Ekološka kriminaliteta in ekološka kriminologija: Praktikum - Eman, Katja (2022)
Environmental Crime and Green Criminology: Practicum. The practicum is a collection of tutorials created after more than 15 years of development of green criminology, research of environmental crime, and teaching of these topics at the undergraduate level at the University of Maribor, Faculty of Criminal Justice and Security. The practicum consists of 23 exercises divided into eight chapters according to the topics. It is a selection of valuable and interesting material for students, with which they consolidate and upgrade the issues presented at the lectures. The purpose of the practicum is to enable students to broaden their horizons and gain additional knowledge. The instructions in the work material encourage them to find things by themselves and connect them with expertise acquired in other subjects. The tutorials are based on real examples from practice and thus enable students to learn more about different forms of responding to environmental harm. The practicum itself is primarily intended for students of the Faculty of Criminal Justice and Security, University of Maribor. Still, at the same time, the material can also be useful for individuals who are interested in this field.
Keywords: green criminology; environmental crime; environmental protection; environmental harm; police